Estudo sócioespacial das áreas de lazer do município de Faxinal do Soturno - RS e o impacto na qualidade de vida da população - Rocha, Ivone Ceretta da (2012)
Health, as well as education and housing, are fundamental rights enshrined in the promulgation of the Brazilian Federal Constitution of 1988, when it moved to live in a period in which the representation of health and healthy living shifted from strictly personal responsibility, to the State and collective, because the status of a fundamental right guaranteed and supported by the State. Thus, the guarantee demanded by that attitudes were taken so that the State could fulfill the commitment they made. Signed on the above, we developed the present study whose theme georeferencing and analysis of leisure facilities in the city of Faxinal do Soturno-RS, highlighting the impacts that these spaces can produce in the quality of life of the population. The study was a literature research and an application of GIS to identified places of entertainment available for the population of Faxinal do Soturno city. Mapping was done and was possible identify 12 locations where people gather to practice physical exercise and leisure. The study revealed that the municipal entity has offered some options, such as the bike path and that, however, these sites need to be better utilized and inserted as important resources for carrying out activities that provide improved quality of life for the population.